Prendre en charge les inégalités environnementales - Nathalie Blanc; Caroline Gallez; Éléonore Genest; Diego Antolinos-Basso; Jean chiche; Hugo Rochard (Développement Durable et Territoires)
Following a plurality of quantitative and qualitative methodologies, and starting from a sampling of four urban territories (Paris 18th, Ivry-sur-Seine, Aubervilliers, Clamart) according to the inequalities observed, the paper aims at studying the evolution of the relations between local authorities and associations and collectives in a context of socio-environmental transition integrating issues of justice. The common denominator of these associations is about addressing environmental and social issues through their repertoires of action: the spectrum extends from the neighborhood recycling center to the solidarity grocery store, including the shared garden involved in popular education. The comparative approach between the four territories analyses the specificities of the mobilizations of associations and collectives with regard to the socio-environmental inequalities of the municipalities.